Emerging Adults and the Use of Textual Digital Communication: A Reflection on Self-Esteem, Loneliness, Anxiety, and Wellbeing - Georgiana Ioana Tamba; Ioana Iancu (Research in Social Sciences and Technology, 2023)
Digital communication is a great facilitator of human connection, positively contributing to life satisfaction and prosocial behavior. However, the existing findings also insist on the drawbacks of the digital communication, as low levels of wellbeing satisfaction, or happiness. Thus, aiming to reconciliate the two sets of assumptions and relying on the reality that textual communication is preferred to voice interaction, the present paper investigates the impact of using messaging apps on the emotional state. More specifically, the study explores if time spent texting, the general affinity towards technology, the perceived ease of use, the perceived usefulness, and the intentional behavior to use messaging applications are correlated with self-esteem, loneliness, anxiety, and wellbeing. An online opinion survey (N=147) with Romanian emerging adults is conducted between February and May 2022. The results show that a positive attitude towards technology is negatively correlated with the feelings of loneliness and anxiety. Moreover, a positive perception on the ease of use and usefulness of the messaging applications is linked with an increased wellbeing.